The Effect of Fermentation Bran and Chitosan in Ration to Percentage of Tegal Duck Digestive Tract Weight - Eli Sahara; Sofia Sandi; Fitra Yossi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Duck productivity is largely determined by the optimization of bodily functions. The food consumed greatly determines the development of digestive organs and internal organs of livestock. Digestive organs that are well developed and function optimally will be very decisive in turning feed into meat and eggs. Chitosan is a crustacean waste product known as animal fiber and is antimicrobial. Whereas fermented bran contains natural fiber rich in nutrients and is hypocholesterol. The aim of the study was to look at the role of chitosan and bran fermented on the weight percentage of digestive organs of ducks. The study used a completely randomized design (CRD) with 4 treatments and 5 replications. Each test consists of 2 ducks as a unit of experiment. The treatment is R0 = 45% corn + 35% concentrate + 20% bran without fermentation, R1 = 45% corn + 35% concentrate + 20% fermented bran, R2 = 45% corn + 35% concentrate + 19.5% fermented bran + 0.5% chitosan and R3 = 45% corn + 35% concentrate + 17.5% fermented + 2.5% chitosan bran. The variable measured is the weight percentage of the digestive organs (gizzard, small intestine and pancreas) in ducks. Data was processed using SAS Windows 16. The results showed that the administration of fermented chitosan and bran gave an average percentage of gizzard weight (ventriculus) and pancreatic weight percentage was not significantly different between treatments (P> 0.05), while treatment R1 (20% fermented bran) It was shown that the percentage of small intestine weight was higher (31.85%) than control R0.